The Effectiveness of Writing Poetry Through Higher Order Thinking Skill (Hots) - Ria Kamilah Agustina; Pipit Ertika Daristin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aim to find out the use of writing poetry through Higher Order Thinking Skill (Hots). This study applied pre-experiment research design to the second year students of English Education Department of Hasyim Asy’ari University. The data were collected through observation and test. The data from observation were analyzed descriptively and the data of the test were analyed stastistically. Based on the results, it showed that there is a significant increase between pretest and posttest scores. The study showed that t count is greater than t table (13.140>2,060). By applying 0,05 level of significance with 26 samples. This means that the alternative hypothesis (Ha) is accepted and the hypothesis (Ho) is rejected.